Toothpaste Gel Preparation from Composite of Hydroxyapatite-Chitosan-Green Betel Leaf (Piper Batle L.) Extract (Indonesian Journal of Chemical Science, 2022)
The use of toothpaste aims to reduce plaque and remineralize tooth enamel as a result of the reduction caused by the activity of oral bacteria. Toothpaste is generally added with antibiotics to treat bacterial caries, but the addition of calcium remineralization compounds to teeth is rarely found so the development of toothpaste with three ingredients, namely hydroxyapatite as an ingredient for remineralization, chitosan, and green betel leaf extract as an antibiotic. The purpose of this study was to manufacture a toothpaste gel formula from the hydroxyapatite-chitosan-green betel leaf extract composite and to determine the physical and chemical properties of each formula. This research is a laboratory experimental research. The results of the organoleptic test showed that the variation of green betel leaf extract affected the color, texture, and aroma of each formula. The homogeneity test showed the homogeneity of the third formula. The third formula has good dispersion between 5-7 cm and good adhesion, which is more than 1 second. The pH test shows that the results of formula one (F1) and formula two (F2) meet the pH range according to SNI (12-3524- 1995) which is 4.5-10 while formula three (F3) is far below it.